2019
DOI: 10.12944/carj.7.3.06
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Constituent’s Comparison Using Various Drying Effects on Rubus Fraxinifolius Pour Leaves

Abstract: Rubus fraxinifolius is a genus that belongs to the Rosaceae family, which grows in the mountainous forests in Indonesia. The study aimed to determine the effects of air-drying (AD) and oven drying (OD) of the young R. fraxinifolius leaves and compare them to the fresh leaves (FL) to observe the phytochemical content and bioactivities. Phytochemical contents of the samples were determined based on qualitative assay, total phenolics, and total flavonoid, whereas bioactivities were evaluated on antioxidant DPPH f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…However, the chemical and biological activities of herbs can be influenced by drying conditions [23,24], and enzymatic reactions in fresh plant cells can impact phytochemical metabolism, resulting in differences in phytochemical content. For example, drying was found to significantly affect the production of characteristic compounds in R. fraxinifolius leaves, with luteolin-7-O-glucuronide, an antioxidant flavonoid glycoside, being detectable in fresh extract but not in oven-dried extract [25]. In contrast, heat treatment was reported to enhance the antioxidant capacity of tamarind leaves by accelerating amine groups that scavenge singlet oxygen [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, the chemical and biological activities of herbs can be influenced by drying conditions [23,24], and enzymatic reactions in fresh plant cells can impact phytochemical metabolism, resulting in differences in phytochemical content. For example, drying was found to significantly affect the production of characteristic compounds in R. fraxinifolius leaves, with luteolin-7-O-glucuronide, an antioxidant flavonoid glycoside, being detectable in fresh extract but not in oven-dried extract [25]. In contrast, heat treatment was reported to enhance the antioxidant capacity of tamarind leaves by accelerating amine groups that scavenge singlet oxygen [26].…”
Section: Discussionmentioning
confidence: 99%
“…The fruit extracts have a weak acetylcholinesterase inhibition activity and moderate antibacterial properties against Staphylococcus aureus, Escherichia coli, and Salmonella enteritidis (Bakar et al 2016). The leaves are found to possess antioxidant properties as well (Desmiaty et al 2018;Dewi et al 2019;Shamsudin et al 2019). Aqueous leaf extracts are potential anti-diabetic remedy and moderate antibacterial agent (Dewi et al 2019) showing partial inhibition for B. cereus (Galvez 2016).…”
Section: Phytochemistrymentioning
confidence: 99%
“…Ripe fruit phytochemical screening shows the presence of saponins, flavonoids, tannins, polyphenols (Barcelo 2015;Galvez 2016), phenolics, anthocyanins, carotenoid (Bakar et al 2016) and quinon (Dewi et al 2019). Secondary metabolite profiling using GC-MS revealed that R. fraxinifolius fruits contain major compounds such as 2(1H)-pyridinone, 6-hydroxy-(14.589%); 1,1,2-triacetoxyethane (10.370%); 2,4-dihydroxy-2,5-dimethyl-3(2H)-furan-3-one (8.283%); and 2-propenoic acid, 2-propenyl ester (3.589%) (Bakar et al 2016).…”
Section: Phytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Phytochemical analysis to detect the presence of alkaloid, flavonoids, triterpenes/steroid, and saponin in the extract using standard methods was carried out using colorimetric methods according to previous study with slight modification (Yadav et al 2011). The total phenolic content was estimated according to Folin-Ciocalteu method and total flavonoid was determined according to aluminums trichloride method using quercetin as the reference compound (Dewi et al 2019).…”
Section: Phytochemical Analysismentioning
confidence: 99%